Research on testing stand with synchronous motor with permanent magnets - Černý, Ondřej; Doleček, Radovan (Univerzita Pardubice, 2008)
The paper deals with the description of research on the testing stand and actual configuration of testing stand last year. This stand was lent by Research Institute of Railway Rolling Stock to Transport Faculty Jan Perner, University of Pardubice. Department of Electrical Engineering, Drive Section has been dealing with research work in field of drive control since 2004. This control will be used at traction drive with traction synchronous motor with permanent magnets (PMSM) for application of rail transport and city local transport in particular. It is also used by Department of Transport Means to research of mechanical properties of contact between wheel and rail. At present these researches are proceeding concurrently. The main goal is a research in field of control of traction PMSM. Advantages of PMSM are known well. The torque from viewpoint of dimension and weigh of drive is the greatest advantage. This characteristic makes possible realization so-called direct drive (i.e. drive of axle or wheels without use of any gearbox) from viewpoint of vehicle construction. Direct drives with other motors (e.g. asynchronous motors) are not possible to place in vehicle because they have too big dimensions. Applications of simple direct drive of wheel simplify the whole construction of low-floor vehicle from mechanical point of view. This simplification of construction leads to time and financial savings from viewpoint of maintenance and other operating costs.
Výzkum na testovacím stendu se synchronním motorem s permanentními magnety
Keywords: synchronní motory; permanentní magnety; trakční pohony; testovací standy